Вплив гідротермальної обробки каталізаторів на їх ефективність у процесі одержання акрилової кислоти та метилакрилату окиснювальною конденсацією метанолу з оцтовою кислотою - Шпирка, Ірина Іванівна; Небесний, Роман Володимирович; Оробчук, Оксана Михайлівна; Халамейда, Світлана В'ячеславівна (НТУ "ХПІ", 2018)
Досліджено процес одержання акрилової кислоти та метилакрилату окиснювальною конденсацією метанолу з оцтовою кислотою в газовій фазі на каталізаторі В₂О₃-Р₂О₅-WO₃-V₂O₅/SiO₂, модифікованому гідротермальним методом в інтервалі температур 100-250 °С. Встановлено вплив температури гідротермальної обробки на селективність та вихід продуктів реакції. Встановлено, що збільшення температури гідротермальної обробки супроводжується збільшенням розміру пор каталізатора, зменшенням селективності утворення акрилової кислоти та збільшенням селективності утворення естерів (метилацетату та метилакрилату). Максимальний сумарний вихід акрилатів (52,9 % за акриловою кислотою та 1,7 % за метилакрилатом) отримано на каталізаторі модифікованому при 150 °С. Гідротермальна обробка каталізатора дозволяє підвищити його ефективність у процесі сумісного одержання акрилової кислоти та метилакрилату окиснювальною конденсацією метанолу з оцтовою кислотою.

The purpose of the work was to investigate the effect of modification of the catalyst of oxidative condensation of methanol with acetic acid on acrylic acid and methyl acrylate selectivity and yield. It was carried out hydrothermal treatment of the support - silica gel, in the temperature range of 100-250 °С in the range of 25 °С. It was investigated the effectiveness of the developed catalyst in the optimal conditions: temperature – 400 °С, reagents ratio CH₃OH: CH₃COOH = 1.2: 1, oxygen concentration in the oxidant stream is 90 % and contact time – 8 seconds. Physical and chemical properties of the catalysts for the process of acrylic acid and methyl acrylate synthesis by oxidative condensation of methanol with acetic acid were determined. Hydrothermal treatment of the silica gel, KSKG brand was performed and based on this treated silica gel catalytic system SiO₂ / B₂O₃-P₂O₅-WO₃-V₂O₅ with the atomic ratio of components В:Р:W:V=3:1:0,18:0,12 were prepared. The catalysts were tested in the process of acrylic acid and methyl acrylate synthesis. It has been established that the best catalyst for the process of acrylic acid and methyl acrylate synthesis is the catalyst with a HTT temperature of 150 °С (under optimum conditions the temperature of the process is 400 ºС and contact time 8 s). At this temperature, it was possible to obtain acrylic acid and methyl acrylate with 54.7 % yield, total selectivity of acrylic acid and methyl acrylate – 97.6 %, acetic acid conversion – 56.9 %. It was established that increasing of hydrothermal treatment temperature leads to increasingof pore size of the catalysts and decreasing the acrylic acid selectivity and increasing of esters (methyl acetate and methyl acrylate) selectivity.
Influence of hydrothermal treatment of catalysts on their effectiveness in the process of acrylic acid and methyl acrylate synthesis via oxidative condensation of methanol with acetic acid
Keywords: гетерогенний каталіз; формальдегід; оцтова кислота; газова фаза; hydrothermal treatment; heterogeneous catalysis